Interior Fragments - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (UI Scholars Hub, 2025)
The critical role of fragments in spatial discourse stems from the complex relationship between fragment and whole. The paradox of fragments offers a deeper understanding of how our architecture, interior, and urban systems are constructed by the presence of fragments and whole and, more importantly, by their interrelationship. Understanding fragments is more than just understanding them as independent spatial entities; it establishes knowledge of how fragments are constructed, connected, and negotiated. This issue of Interiority presents a collection of inquiries on fragments within various everyday interior contexts and representations, demonstrating the emergence of spatialities that celebrate interconnection possibilities beyond the independent parts. The articles in this issue present inquiries into fragments, demonstrating the role of fragments in constructing relationships, building narratives and layers of interconnections, and establishing deeper meanings in various interior phenomena and representational media.